Analysis of Mycobacterium tuberculosis and Physical Condition of The House with Incidence Pulmonary Tuberculosis - Evin Kenedyanti; Lilis Sulistyorini (Jurnal Berkala Epidemiologi, 2017)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis bacteria and often attacks lung tissue. Based on observations, the condition of settlements in the Mulyorejo District is very dense and sanitation is not good. This can lead to the occurrence of environmental-based diseases, namely pulmonary TB disease. This research is observational research with a case-control study design. Analysis of the data used is to see the value of OR (Odds Ratio). This research was conducted at the Public health center (PHC) of Mulyorejo on May 23 - November 23, 2016. The sampling technique uses purposive sampling with a ratio of 1: 2, namely 5 houses with pulmonary tuberculosis and 10 houses without pulmonary tuberculosis. Data collection using observation sheets, measurement of physical quality of air, and air sampling using the Haz-Dust model EPAM-5000, then dust samples were sent to the Institute of Tropical Diseases Airlangga University for the examination of Mycobacterium tuberculosis bacteria in the air with PCR Aerosol. Data analysis uses the distribution of frequency tables and crosstab. The results showed that Mycobacterium tuberculosis in the air (OR = 2.667) and physical condition of the home (OR = 2.667) were risk factors for pulmonary TB. It is suggested that the community should improve the physical condition of the house, especially the addition of mechanical ventilation to facilitate air circulation because ventilation affects the temperature and humidity, for houses whose walls are close to neighboring walls can make air vents on the roof. Further research is needed by using more samples and research is needed to find out the factors that cause the Mycobacterium tuberculosis bacteria in the air in the respondent's house both patients and non-patients.